(3Mce hCeKGd GdYGde HGdEfLdjRjI hHGdYQHjI (B/s - (3fGUja, TGOjs; (3SYO, Wg YHO GdQDhas ((3OeTb (B:s (3GdbGgQI (B:s (3OGQ GdcJGH GdYQHj , s, 2010)
(3GdMce hGdCeKGd gj YUGQI JLGQH GdTYhH hPGcQJgG hdcd TYH KbGaJg GdJj dG JNdh ef MceI hCeKGdg GdJj jJe GfJTGQgG hJOGhdgG ef Ljd Edi Ljd dJchf CcKQ CTcGd GdJYHjQ GdTYHjI SMQG hJCKjQG HbhI eYGfjgG hEjLGR fUgG hLeGdg hbOQGJgG Ydi GdfaGP aj CaFOI hYbhd GdfGS QZe Cf GdMceI hGdeKGd cdjgeG ef LhGeY Gdcde EdG Cf GdMceI JajO eYfi hGMOG HjfeG jajO GdeKd eYfjjf XGgQG hHGWfG CeG GdXGgQ agh eG jMedg ef ETGQI JGQjNjI Edi MGOK eYjf cGf SHH XghQg hCeG GdHGWf agh eG jajO eYfGg ef MceI hEQTGO hJTHjg hJUhjQ aGdMceI EPf JJVef ehYVI Ch fUjMI Ch YHQI(B.s
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdCeKGd GdYQHjIs; (3GdCeKGd GdEfLdjRjIs